The Role of Instagram as a Promotional Media in Bananakong Blitar Food Product Sales - Aldita Wahyu Widya Nuringtyas; Andiwi Meifilina; Ferida Asih Wiludjeng (Universitas Islam Balitar, 2023)
The presence of social media has now changed the way a person thinks and acts in everyday life. Social media can be used for broader, strategic and interactive two-way communication practices. In this modern era, each of us has our own social media such as; facebook, instagram, whatsapp, twitter, and others. With social media, we get carried away by trends that make us who we are. The problem with this research is that there are many culinary business competitors, especially processed food products from bananas in Blitar City due to the development of viral banana processed food businesses, making culinary business people open these businesses to meet their needs. This is worth researching because with many competitors, it can cause a decrease in sales turnover. So a strategy is needed to increase sales turnover, namely by creating new products that are attractive and meet consumer needs and we all know that the role of marketing, especially now in the digital era, will have an influence. One way is to use an Instagram account. The role of Instagram is very important for new business people and old business people, because promotion via Instagram is better known to a wider audience. The problem formulation is what is the role of Instagram as a promotional medium for the sale of Blitar bananakong food products. This research aims to analyze the role of Instagram as a promotional media for the sale of Blitar bananakong food products. In this study using a qualitative descriptive method and using a purposive sampling technique in collecting informants. Data collection uses the following techniques: 1) Observation, 2) Interview, 3) Documentation. The results of this research are the role of Instagram as a promotional medium for the sale of Blitar bananakong food products, that the Instagram application has a very important role in an online business/business to promote and advertise the products or services being sold to customers and potential customers to buy products or services. which is offered. Customers will inform family or relatives about bananakong products and provide testimonials regarding taste, variants and prices and ensure that Blitar bananakong products are really delicious and have a distinctive taste. Postings on the Blitar bananakong Instagram account can attract customers' buying interest because every post about the Blitar bananakong menu variant really makes customers tempted to try and buy Blitar bananakong products. However, the Instagram application sometimes experiences problems such as the network and application not responding/lag. Therefore, the owner overcomes problems like this by deleting the cache and waiting a few minutes so he can use the Instagram application again.